Regional Variation in Inequality of Educational Opportunity across Europe. (July 2021) - Betthäuser, Bastian A.; Kaiser, Caspar; Trinh, Nhat An
A large body of literature documents cross-national variation in the level of inequality of educational opportunity (IEO) among children from different social backgrounds. By contrast, relatively little attention has been given to the extent to which IEO varies within counties and across regions. On the basis of data from the European Social Survey, the authors map variation in IEO across regions in Europe and show that IEO varies substantially within counties. This visualization of the heterogeneity of IEO within European countries highlights the need for researchers and policy makers to extend the current focus on cross-national differences and to investigate and address IEO at the regional level. The visualization raises important questions with respect to the contours, causes, and consequences of cross-regional variation in IEO.